S130 HIV-1 infection of macrophages dysregulates pro-inflammatory host responses to Mycobacterium tuberculosis through inhibition of interleukin 10. (2nd December 2011) - Tomlinson, G S; Elkington, P T G; Bell, L; Walker, N F; Tsang, J; Brown, J; Breen, R; Lipman, M; Katz, D R; Miller, R F; Chain, B M; Noursadeghi, M
Abstract : Introduction: Human immunodeficiency virus (HIV)-1 greatly increases the risk of active Mycobacterium tuberculosis (Mtb) infection. Both pathogens target macrophages by evading innate immune recognition or intracellular killing. Since macrophages play a key role in inflammatory responses and their resolution, we tested the hypothesis that HIV-1 infection of macrophages may modulate inflammatory responses to co-infection with Mtb contributing to the immunopathogenesis of active tuberculosis (TB). Methods: Innate immune responses to Mtb were assessed in human macrophages with and without productive HIV-1 infection using genome-wide transcriptional profiling. Array data were validated by quantitative PCR and correlated with protein secretion in cell culture supernatants. The effects of Mtb co-infection on HIV replication were assessed by ELISA. The mechanisms underlying the observed phenotype were examined by Western immunoblotting and using selective inhibitors of innate immune signalling pathways. Results: HIV-1 infection of monocyte-derived macrophages leads to sustained, exaggerated pro-inflammatory responses to Mtb co-infection, including cytokines and chemokines that may recruit and activate further inflammatory leucocytes, and matrix metalloproteinases which play a role in tissue destruction. This phenotype is associated with rescue of HIV-1 replication following early repression in response to Mtb. Our data suggest that augmented inflammatory responses to Mtb result from deficient induction of anti-inflammatory interleukin-10 in HIV-1 infected cells. None of these changes were evident in HIV-1 infected macrophages co-infected with Streptococcus pneumoniae, and the specificity of the effect in Mtb co-infection was mirrored by lower IL-10 and higher pro-inflammatory IL-1β in respiratory samples from HIV-1 infected patients with pulmonary TB compared to non-tuberculous respiratory infection. Complementation of deficient IL-10 responses to Mtb in HIV-1 infected macrophages reverses the exaggerated pro-inflammatory phenotype. HIV-1 infection attenuates phosphorylation of p38 and ERK1/2 in mitogen activated kinase pathways involved in IL-10 induction downstream of TLR2 and dectin-1 receptor stimulation. IL-10 production in HIV-1 infected cells is also inhibited in response to zymosan stimulation of these pathways. Inhibition of virus maturation with HIV-1 protease inhibitors, does not affect attenuation of IL-10 responses. Conclusions: Deficient induction of homeostatic IL-10 and consequent augmentation of pro-inflammatory responses may contribute to the immunopathogenesis of active TB and propagation of virus infection in HIV-1/Mtb co-infection.